Plant water relations and edaphoclimatic conditions affecting acorn production in a holm oak (Quercus ilex L. ssp. ballota) open woodland (Agroforestry Systems, 2009)
Acorn production patterns and the annual evolution of water relations parameters of Quercus ilex ssp. ballota (Desf.) Samp. in a dehesa (an open woodland forest) subject to various soil treatments (ploughing, ploughing? sowing, control) were studied in southwest Spain from June 2006 to December 2008. The effects of soil water holding capacity and effective soil depth on soil and plant water status and acorn production were also investigated. Water parameters showed signiÞcant differences between the ploughing treatment and the control, and there were also signiÞcant temporal differences. Xylem water potential ranged from- 3.4 ± 0.1 to - 0.7 ± 0.2 MPa, and cuticular transpiration was 62.4Ð 192.9 mmol H2O kg - 1 s - 1 . Acorn production did not differ signiÞcantly according to soil treatment, and showed large intra-speciÞc variability. Individual values ranged from 0 to 1,220 g m - 2 (fresh weight). Positive relationships were found between xylem water potential, cuticular transpiration and relative water content measured at midsummer, and acorn production during the three studied years. These results suggest that climatic conditions and soil water availability have a strong inßuence on plant water status, and therefore on acorn development during summer. The results also reßect the ability of this species to adapt to the Mediterranean climate by preserving water during dry periods, which to a large extent can be attributed to stomatal closure at high relative water content levels, an